Study of clinical profile and management of varicose veins in the department of surgery - Jaykar, Ritvik D.; Jadhav, Sachin C.; Chaudhari, Vivek M. (International Surgery Journal, 2021)
Background: Varicose veins are common problem and are present in at least 10% of the general population. So far as the aetiology is concerned varicose veins mostly occur due to incompetence of their valves. Risk factors for varicose veins include obesity, female sex, inactivity, and family history. Varicose veins do not threaten life and are seldom disabling, but it causes a considerable demand on medical care. Methods: The study was prospective observational single center study. 30 patients were selected for the study which fit in the selection criteria laid down at the beginning of the study. Informed consent was obtained from each patient before any investigations and treatment. Results: The study revealed that the varicose veins of lower limbs are a disease of younger age group, occurring more commonly during third and fifth decades of life. The involvement of long saphenous system was more common. Conclusions: Results of our study are comparable with various other studies in literature.